2024
DOI: 10.1038/s41598-024-56520-5
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput gut-on-chip platform to study the epithelial responses to enterotoxins

Moran Morelli,
Marta Cabezuelo Rodríguez,
Karla Queiroz

Abstract: Enterotoxins are a type of toxins that primarily affect the intestines. Understanding their harmful effects is essential for food safety and medical research. Current methods lack high-throughput, robust, and translatable models capable of characterizing toxin-specific epithelial damage. Pressing concerns regarding enterotoxin contamination of foods and emerging interest in clinical applications of enterotoxins emphasize the need for new platforms. Here, we demonstrate how Caco-2 tubules can be used to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Significantly, the presence of epithelial cells enhanced the density and directivity of neuronal processes. In another membrane-free chip, Morelli et al observed enterotoxin-induced damage to the human intestinal epithelium, showing a dose-dependent reduction in barrier permeability [ 144 ]. Overall, membrane-free chips can visually dissect the neuroepithelial connections, injury and recovery of functional barriers between the gut and other organs.…”
Section: Microfluidic Strategies For the Construction Of Intestinal B...mentioning
confidence: 99%
“…Significantly, the presence of epithelial cells enhanced the density and directivity of neuronal processes. In another membrane-free chip, Morelli et al observed enterotoxin-induced damage to the human intestinal epithelium, showing a dose-dependent reduction in barrier permeability [ 144 ]. Overall, membrane-free chips can visually dissect the neuroepithelial connections, injury and recovery of functional barriers between the gut and other organs.…”
Section: Microfluidic Strategies For the Construction Of Intestinal B...mentioning
confidence: 99%